2015
DOI: 10.1111/jvim.13584
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Diabetes Mellitus in Insured Swedish Cats in Relation to Age, Breed and Sex

Abstract: BackgroundDiabetes mellitus (DM) is a common endocrinopathy in cats. Most affected cats suffer from a type of diabetes similar to type 2 diabetes in humans. An increasing prevalence has been described in cats, as in humans, related to obesity and other lifestyle factors.ObjectivesTo describe the incidence of DM in insured Swedish cats and the association of DM with demographic risk factors, such as age, breed and sex.AnimalsA cohort of 504,688 individual cats accounting for 1,229,699 cat‐years at risk (CYAR) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
51
1
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 27 publications
3
51
1
1
Order By: Relevance
“…Similarities between type 2 diabetes in cats and people include common risk factors, such as obesity, age, and physical inactivity, as well as similar pathophysiological findings, including deposition of amyloid in islets . Other risk factors associated with increased risk of DM in cats include male sex, neutering, indoor confinement, and treatment with certain drugs …”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Similarities between type 2 diabetes in cats and people include common risk factors, such as obesity, age, and physical inactivity, as well as similar pathophysiological findings, including deposition of amyloid in islets . Other risk factors associated with increased risk of DM in cats include male sex, neutering, indoor confinement, and treatment with certain drugs …”
mentioning
confidence: 97%
“…Diabetes mellitus (DM) in cats has an incidence of 11.6 cases per 10,000 cat‐years at risk . Most cats suffer from a type of DM similar to type 2 diabetes (T2DM) in people, characterized by a relative deficiency of insulin secretion combined with insulin resistance, in contrast to the primary beta‐cell deficiency of type 1 diabetes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A genetic component for DM in cats is also indicated by specific feline breeds appearing to be at increased or decreased risk of DM. Several studies have identified an increased risk of DM in Burmese cats in the United Kingdom, Europe, and Australia, and a recent Swedish investigation demonstrated an increased risk in Norwegian Forest cats, Russian Blues and Abyssinians, and a decreased risk in Persians . An increased risk for DM has not been documented in American Burmese cats, which has been attributed to American Burmese being genetically distinct from Burmese in other parts of the world …”
mentioning
confidence: 99%
“…Several studies have identified an increased risk of DM in Burmese cats in the United Kingdom, Europe, and Australia, and a recent Swedish investigation demonstrated an increased risk in Norwegian Forest cats, Russian Blues and Abyssinians, and a decreased risk in Persians. 2,17,18 An increased risk for DM has not been documented in American Burmese cats, which has been attributed to American Burmese being genetically distinct from Burmese in other parts of the world. 19 The only previous study to investigate risk factors for DM in cats in England analysed a modest-sized insured population of 14,030 cats.…”
mentioning
confidence: 99%